2016
DOI: 10.1038/cddis.2016.194
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-205 targets VEGFA and FGF2 and regulates resistance to chemotherapeutics in breast cancer

Abstract: MicroRNAs (miRNAs) have critical roles in regulating cancer cell survival, proliferation and sensitivity to chemotherapy. The potential application of using miRNAs to predict chemotherapeutic response to cancer treatment is highly promising. However, the underlying mechanisms of chemotherapy response control by miRNAs remain to be fully identified and their prognostic value has not been fully evaluated. Here we show a strong correlation between miR-205 expression and chemosensitivtiy to TAC (docetaxol, doxorub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
87
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(91 citation statements)
references
References 62 publications
(79 reference statements)
4
87
0
Order By: Relevance
“…20 Moreover, recent study reports that miRNA-205 enhances breast cancer cell resistance to doxorubicin and taxol by targeting VEGFA and FGF2. 21 …”
mentioning
confidence: 99%
“…20 Moreover, recent study reports that miRNA-205 enhances breast cancer cell resistance to doxorubicin and taxol by targeting VEGFA and FGF2. 21 …”
mentioning
confidence: 99%
“…Our previous studies have demonstrated that miRNAs have a vital role in EPC function . Additionally, miR‐205 has been shown to have different effects on angiogenesis and migration in different types of tumours . Meanwhile, miR‐205 promotes wound healing in human corneal epithelial cells .…”
Section: Discussionmentioning
confidence: 99%
“…11,[27][28][29][30] Additionally, miR-205 has been shown to have different effects on angiogenesis and migration in different types of tumours. [32][33][34][35]42 Meanwhile, miR-205 promotes wound healing in human corneal epithelial cells. 31 However, the role and underlying mechanism of miR-205 in DVT and EPCs, particularly in regulating angiogenesis and thrombus resolution, remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, we performed a search in PubMed for these 14 miRNAs and found that 7 of them had been confirmed experimentally to target VEGFA, that is, miR-361 [40, 41], miR-140 [42], miR-15a [43], miR-15b [44], miR-205 [45], miR-206 [46], and miR-200c [47]. Therefore, we speculate that these miRNAs may target VEGFA and play a role in NSC behavior under hypoxia.…”
Section: Discussionmentioning
confidence: 99%